Sosialisasi Penanganan Banjir Sungai Di Kabupaten Luwu - Muhammad Farid Maricar; Rita Lopa; Farouk Maricar; Saleh Pallu; Arsyad Thaha; Bambang Bakri; Ahmad Sumakin; Mukhsan Hatta; Silman Pongmanda; Riswal Karama; Subhan Mustari; Ildha Dwi Puspita; Aslamil Taqwa (Faculty of Engineering UNHAS, 2021)
Luwu Regency is one of the districts in South Sulawesi Province where the most frequent disasters are floods and landslides, which causes flash flood in several places in Luwu Regency. UNHAS River School now entering its 5th year. Various activities have been carried out including inviting all communities to act together and understand the needs of the river. This Community Service activity is carried out in 2 phases; the stage of discussion and site observation. The discussion method was the river school socialization and Focus Group Discussions to determine the response and mitigation of the community on high risk flood area. The implementation of river school activities contributes to increasing community knowledge and understanding of how to handle river floods. Armed with the knowledge and understanding skills transmitted by the PKM UNHAS team, it is hoped that the pattern of community behavior regarding the regulation of river boundaries, garbage, etc. can be applied and have a positive impact on improving river management by the community, in order to achieve a clean, healthy, and sustainable river without flood.